2012
DOI: 10.1093/brain/aws256
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to surface dopamine-2 receptor in autoimmune movement and psychiatric disorders

Abstract: Recent reports of autoantibodies that bind to neuronal surface receptors or synaptic proteins have defined treatable forms of autoimmune encephalitis. Despite these developments, many cases of encephalitis remain unexplained. We have previously described a basal ganglia encephalitis with dominant movement and psychiatric disease, and proposed an autoimmune aetiology. Given the role of dopamine and dopamine receptors in the control of movement and behaviour, we hypothesized that patients with basal ganglia ence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
307
2
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(326 citation statements)
references
References 53 publications
8
307
2
9
Order By: Relevance
“…27 Antibodies to D2R were found in only 4 patients with dystonia-Parkinsonism and basal ganglia lesions, representing a small subgroup (2%). 16 There were no patients with antibodies to glutamic acid decarboxylase and only 1 patient with glycine R antibody (who also had VGKC-complex antibodies and Mycoplasma), and reported pediatric cases with these antibodies are rare. Nine (20%) of the patients with unknown encephalitis did not have serum available for autoantibody testing, and comprehensive testing may help to ensure recognition of known autoantibodies and to define some of the "unknown" patients in the future.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…27 Antibodies to D2R were found in only 4 patients with dystonia-Parkinsonism and basal ganglia lesions, representing a small subgroup (2%). 16 There were no patients with antibodies to glutamic acid decarboxylase and only 1 patient with glycine R antibody (who also had VGKC-complex antibodies and Mycoplasma), and reported pediatric cases with these antibodies are rare. Nine (20%) of the patients with unknown encephalitis did not have serum available for autoantibody testing, and comprehensive testing may help to ensure recognition of known autoantibodies and to define some of the "unknown" patients in the future.…”
Section: Discussionmentioning
confidence: 96%
“…16 Three patients had acute necrotizing encephalopathy with the typical radiologic features. 18,20 There were no other…”
Section: Subgroup Analysismentioning
confidence: 99%
“…A genome-wide association study identified genetic variation in the DRD2 gene locus as being associated with schizophrenia risk (16). In patients with encephalitis and clinical symptoms related to psychosis, autoantibodies against DRD2 have been identified (17). Although these human experiments of nature were not used in the development of antipsychotic medications to treat schizophrenia, they do provide PoC that mechanistic data from human genetics and tissue-specific autoimmunity can, in retrospect, identify the in vivo targets of approved drugs.…”
Section: Causal Human Biologymentioning
confidence: 99%
“…We used fluorescence-activated cell sorting (FACS) analysis to detect antibody binding of patient serum IgG to surface MOG transduced in HEK293 cells as we have previously described (methodology presented in appendix e-2). 30,31 Samples were considered positive if they were above threshold on at least 2 of 3 repeated experiments, and the intraassay variation is summarized in appendix e-2. Classification of evidence.…”
mentioning
confidence: 99%